Synergistic Effects of Drivers on Spatiotemporal Changes in Carbon and Water Use Efficiency in Irrigated Cropland Ecosystems - Guangchao Li; Zhaoqin Yi; Tiantian Qian; Yuhan Chang; Hanjing Gao; Fei Yu; Liqin Han; Yayan Lu; Kangjia Zuo (Agronomy)
Understanding the spatiotemporal patterns of cropland carbon and carbon water use efficiency (CWUE) and its driving factors is essential for sustainable agricultural development. Based on a multi-source remote sensing dataset, this study applies a trend analysis (Sen + Mann–Kendall), a dual-type randomized extraction algorithm, and an optimized XGBoost model to examine the spatiotemporal variations in cropland CWUE, including the water use efficiency of net primary production (WUENPP), water use efficiency of gross primary production (WUEGPP), and carbon use efficiency (CUE) in Henan Province from 2001 to 2019. This study further quantifies the impact of irrigation on the cropland CWUE and explores the synergistic effects of its driving factors in irrigated areas. Results reveal significant regional differences in cropland CWUE across Henan Province. Higher multi-year average values of CUE and WUENPP were observed in the western region, while the WUEGPP was more prominent in the south-central region. Over 76% of cropland areas showed a general downward trend in three indicators, with significant interannual declines. Non-irrigated cropland exhibited higher CWUE values than irrigated ones. The average values over multiple years of the WUEGPP, WUENPP, and CUE of irrigated cropland were 2.51 <semantics>g C m−2 mm−1</semantics>, 1.08 <semantics>g C m−2 mm−1</semantics>, and 0.43, respectively. Sunlight was the dominant factor influencing the WUEGPP in irrigated areas, while precipitation primarily regulated the WUENPP and CUE. The influence of the gross domestic product (GDP) was found to be minimal. Notably, both the leaf area index (LAI) and precipitation exhibited a shift from a positive to negative influence on CUE once their values exceeded optimal thresholds, indicating that resource overabundance can lead to physiological limitations. This study offers valuable insights into how irrigated cropland responds to the combined effects of multiple environmental and socio-economic drivers.